The Antibacterial Activity Evaluation of the Nanoparticles of Silver on Acinetobacter Baumannii - Seyedeh Nasim Karimipour; Asghar Tanomand; Sadegh Rostamnia (Fasa University of Medical Sciences, 2016)
Background & Objective: Due to the high drug resistance in Acinetobacter baumannii, in this research, antibacterial properties of nano silver was evaluated for Acinetobacter baumannii. Materials & Methods: The nano silver with approximate diameter of 20 nanometer from Pishtazan Inc. Mashad, Iran and 5 nanometer from the Department of Chemistry in Maragheh University were prepared. Its concentration was determined by spectroscopy method in Tabriz Chemistry University.  Antimicrobial effects were determined by Mean Inhibitory Concentration (MIC) and Minimal Bacterial Concentration (MBC) by micro-broth-dilution method, disc diffusion and well diffusion methods. Anti-bacterial activity of nano-silver was tested for Acinetobacter baumannii NCTC12516 on 20 clinical strains (collected from Imam Reza Hospital in Tabriz). Results: The results showed the MIC and MBC of 20nm nanoparticles were 1250 ppm and 2500 ppm, respectively. On the other hand, the MIC and MBC of 5 nm nanoparticles were 156 ppm and 312 ppm, respectively. According to these findings, the MIC and MBC identified for clinical Acinetobacter baumannii strains under study along with the NCTC12516 strain did not show a significant difference. Yet the amount of inhibition for the 20nm nanoparticles in the density of 20000 ppm of clinical Acinetobacter baumannii and NCTC12516 strains was 11 millimeter with the disc diffusion method and 9.5 millimeter for the well diffusion method with the same concentration. The amount of inhibition of 5nm nanoparticles in the 250-ppm concentration with both disc diffusion and well diffusion methods was 9.5 millimeter. Conclusions: Acinetobacter baumannii is susceptible to nano-silver. Also the same MIC and MBC in multiple clinical strains suggests that there is not resistance to silver nanoparticles in Acinetobacter baumannii